2018
DOI: 10.18632/oncotarget.26025
|View full text |Cite
|
Sign up to set email alerts
|

Trisenox disrupts MDM2-DAXX-HAUSP complex and activates p53, cell cycle regulation and apoptosis in acute leukemia cells

Abstract: Trisenox (TX) has been used in the treatment of both de novo and relapsed acute promyelocytic leukemia (APL) patients. Using in vitro APL cell lines model in this research, we report on a new target of TX action through disruption of MDM2-DAXX-HAUSP complex, degradation of MDM2, and activation of p53 expression. TX–induced stress signal was transmitted by protein kinase (ATM & ATR) and phosphorylation of its downstream targets CHK1, CHK2, ATM, and ATR, respectively at the Ser 345, Thr68, Ser1981 and Ser 428 re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
27
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 9 publications
(32 citation statements)
references
References 55 publications
5
27
0
Order By: Relevance
“…Similarly, our finding also shows that TX caused genotoxicity in mice APL liver tissue (2B[i-v]). Accumulating evidence suggests that the DNA damage signal is transmitted by protein kinase (ATM& ATR) and its residues phosphorylation leading to disruption of MDM2-DAXX-HAUSP complex and activation of p53 (12,15,35). Our findings show that TX-induced genotoxic damage was transmitted by reduced ATM and stimulated ATR expression along with phosphorylation of CHK1 residue at ser 345 residue in mice APL liver tissue (Fig.3A).…”
Section: Discussionsupporting
confidence: 50%
See 3 more Smart Citations
“…Similarly, our finding also shows that TX caused genotoxicity in mice APL liver tissue (2B[i-v]). Accumulating evidence suggests that the DNA damage signal is transmitted by protein kinase (ATM& ATR) and its residues phosphorylation leading to disruption of MDM2-DAXX-HAUSP complex and activation of p53 (12,15,35). Our findings show that TX-induced genotoxic damage was transmitted by reduced ATM and stimulated ATR expression along with phosphorylation of CHK1 residue at ser 345 residue in mice APL liver tissue (Fig.3A).…”
Section: Discussionsupporting
confidence: 50%
“…It has been reported that DNA damage disrupts MDM2-DAXX-HAUSP complex leading to activation of p53 and MDM2 degradation in many cancer cells (12,15,35). Our findings reveal that TX reduced MDM2 expression in a dose dependent fashion (Fig.4A&B[i-v]), leading to p53 activation in APL mice bone marrow cells.…”
Section: Tx Activates P53 In Apl Mice Bone Marrow Cellssupporting
confidence: 57%
See 2 more Smart Citations
“…In addition, we also found that endogenous DAXX mRNA expression was upregulated soon after exposure to UV irradiation; however, total protein levels were not elevated as expected, consistent with a microarray experiment showing that DAXX mRNA is upregulated in breast cancer cells upon exposure to curcumin relative to that in mammary epithelial cell lines 25 . Moreover, a previous study showed that DAXX is phosphorylated rapidly to induce p53 activation in response to DNA damage through the ataxia telangiectasia mutated(ATM)/Ataxia telangiectasia and Rad3 related (ATR) signaling pathway 26 . Therefore, we postulated that DAXX may play an intrinsic role in the DNA damage-induced response depending on the level of phosphorylation.…”
Section: Discussionmentioning
confidence: 99%